2019
DOI: 10.1038/s41394-019-0154-3
|View full text |Cite
|
Sign up to set email alerts
|

The impact of personal and environmental factors on the rehabilitation of persons with neglected spinal cord injury in Malaysia

Abstract: Introduction Managing neglected spinal cord injury (SCI) patients in a rural setting can be challenging due to a lack of resources and the unique personal and environmental contextual factors that may hinder rehabilitation. This article aims to identify the contextual factors and their impact on successful rehabilitation. Case presentation A middle-aged man from a rural area had suffered a neglected traumatic SCI and was first seen by the rehabilitation team 17 years post injury. He had a T7 AIS A paraplegia a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(8 citation statements)
references
References 12 publications
0
1
1
Order By: Relevance
“…In contrast, other studies have reported premature discharge during the first admission or inadequate management as predominant causative factors in developing countries, and missed diagnosis as the predominant cause in Western countries. 3 , 9 , 23 , 24 The mean duration of neglect was 43 days in our study, whereas most patients included in the study by Chhabra et al. presented after 168 days.…”
Section: Discussioncontrasting
confidence: 45%
“…In contrast, other studies have reported premature discharge during the first admission or inadequate management as predominant causative factors in developing countries, and missed diagnosis as the predominant cause in Western countries. 3 , 9 , 23 , 24 The mean duration of neglect was 43 days in our study, whereas most patients included in the study by Chhabra et al. presented after 168 days.…”
Section: Discussioncontrasting
confidence: 45%
“…Nepal is home to many ethnic groups, each with its own distinct cultures and religious practices (Malla et al, 2015). Consistent with the findings of Hanapi et al (2019), traditional medical practices are still extensively used in most parts of Nepal. The utilization of Ayurveda or medicinal herbs, oil massages, and the application of heated bricks to relieve pain are common practices in Nepal (Shankar et al, 2006;Thapa et al, 2018).…”
Section: Nepalese Cultural Beliefs and Practices On Rehabilitationmentioning
confidence: 71%
“…Early rehabilitation not only prevents future complications but enhances the quality of life for PwSCI by maximizing their independence, promoting participation in life activities, and improving psychological well-being (Dhakal et al, 2022;Hachem et al, 2017;Nas et al, 2015). However, several challenges hinder effective rehabilitation services for PwSCI, especially in resource-limited countries (Burns & O'Connell, 2012;Hanapi et al, 2019;Uddin et al, 2022).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Two small qualitative studies conducted in Mongolia and Malaysia showed that participation restrictions were associated with insufficient accessibility of the natural and built environments, transportation, and lack of health care services. 13 , 14 A study by Reinhardt and colleagues compared environmental factors reported in low and high resourced settings and found that fewer facilitators and more barriers were experienced in lower-resourced countries. 15 More recently, Reinhardt and associates compared environmental barriers experienced by people with SCI across 22 countries including China using data from the International Spinal Cord Injury Community Survey (InSCI) on which also the present study is based, In this study, more barriers were experienced in countries with greater overall income inequality and lower average household income of those with SCI, among others.…”
Section: Introductionmentioning
confidence: 99%